2018
DOI: 10.1556/1886.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Leptospira infection in backyard pigs in Durango State, Mexico

Abstract: PurposeThis study aimed to determine the seroprevalence and correlates of Leptospira IgG antibodies in backyard pigs in the northern Mexican state of Durango. We performed a cross-sectional study of 305 backyard pigs. Anti-Leptospira IgG antibodies were detected using microscopic agglutination assay (MAT) with a panel of 12 Leptospira antigens.ResultsOverall, antibodies against Leptospira (any of the 12 Leptospira serovars examined) were found in 186 (61.0%) of the 305 pigs studied. Seropositive pigs were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…On the other hand, a low geographical elevation was related to the presence of anti-Leptospira sp. antibodies, which is in agreement with previous studies carried out in dogs and pigs, although the level of the geographical scale of the study of the variable may change its positive relationship (Cruz-Romero et al, 2018;Gracie et al, 2014;Major et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, a low geographical elevation was related to the presence of anti-Leptospira sp. antibodies, which is in agreement with previous studies carried out in dogs and pigs, although the level of the geographical scale of the study of the variable may change its positive relationship (Cruz-Romero et al, 2018;Gracie et al, 2014;Major et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, anti-Leptospira spp. antibodies were detected in 59.3% of the pigs tested, which is a high prevalence, 2-3 times higher compared to similar studies performed in Italy [32] and Germany [33], and close to that reported by Cruz-Romero et al from small households in Mexico [34].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, detection of antibodies against Djasiman and Icterohaemorrhagiae serogroups evidenced additional exposure to sources contaminated with leptospires shed by synanthropic or wild mammals 3,29 . Regarding different species of L. interrogans serogroups, this study showed a high frequency of seroprevalent and seroincident cases against the Tarassovi serogroup, which is mainly found in pigs 3,30 . Even though the Tarassovi serogroup is present in different species of Leptospira considered as pathogens and classified into subgroup II, this serogroup has not been incriminated in clinical cases of leptospirosis in humans yet 43 .…”
Section: Discussionmentioning
confidence: 64%
“…Our analysis showed that the tenancy of piglets and the eyesight of opossums in the peridomiciliary area were important risk factors for seroprevalent cases, and the presence of a dirt floor inside households was associated with both seroprevalent and seroincident cases of Leptospira infection. Other studies have identified the presence of piglets and opossums in the peridomiciliary area as risk factors for Leptospira infection; these mammals have been considered as potential hosts participating in the life cycles of several Leptospira species 3,29,30 . Also, Bierke et al 31 found that Leptospira can survive for long periodsin several types of soil depending on its physical, chemical, and biological conditions such as pH, temperature, or mineral concentration.…”
Section: Discussionmentioning
confidence: 99%